Phenotyping a Dynamic Trait: Leaf Growth of Perennial Ryegrass Under Water Limiting Conditions - Yates, Steven; Jaškūnė, Kristina; Liebisch, Frank; Nagelmüller, Sebastian; Kirchgessner, Norbert; Kölliker, Roland; Walter, Achim; Brazauskas, Gintaras; Studer, Bruno (Frontiers in Plant Science, 2019)
Water limitation is one of the major factors reducing crop productivity worldwide. In order to develop efficient breeding strategies to improve drought tolerance, accurate methods to identify when a plant reduces growth as a consequence of water deficit have yet to be established. In perennial ryegrass (Lolium perenne L.), an important forage grass of the Poaceae family, leaf elongation is an important factor determining plant growth and hence forage yield. Although leaf elongation has been shown to be temperature-dependent under non-stress conditions, the impact of drought on leaf elongation in perennial ryegrass is poorly understood. We describe a method for quantifying drought tolerance based on leaf elongation in relation to temperature and soil moisture, developed on the basis of drought stress experiments in perennial ryegrass. With decreasing soil moisture, three growth response phases were identified: First, a “normal” phase where growth is mainly determined by temperature, second a “slow” phase where leaf elongation decreases proportionally to soil water potential and third an “arrest” phase where leaf growth terminates. A custom R function was able to quantify the points which demarcate these phases and can be used to describe the response of plants to water deficit. Applied to different perennial ryegrass genotypes, this function revealed significant genotypic variation in the response of leaf growth to temperature and soil moisture. Dynamic phenotyping of leaf elongation can be used as a tool to accurately quantify drought tolerance in perennial ryegrass and to improve this trait by breeding. Moreover, the tools presented here are applicable to study the plant response to other stresses in species with linear, graminoid leaf morphology.